PEMASARAN KUE CUCUR CERIA MELALUI OTR (ON THE ROAD) DI KABUPATEN PONOROGO BERDASARKAN PRINSIP SYARIAH - YULINDA DARWIYANTI; Tri Eka Pujilestari (INAIFAS Press, 2026)
This study aims to determine the marketing strategy of Ceria Cucur cakes through OTR (On The Road) in Ponorogo Regency. The focus of this study is to understand the role of OTR (On The Road) in increasing sales. This study uses a qualitative research method that focuses on facts that occur in the field with an inductive and descriptive or explanatory approach. Data was collected through interviews with the owner of Cucur Ceria cakes. The findings of this study indicate that with SWOT analysis, marketing Cucur Ceria cakes through OTR can increase sales turnover, identify areas with high demand for opening new branches, eliminate the need for renting a place, and reach more customers. The results of this study also show that selling through OTR has many challenges and shortcomings, such as competitors who dislike sellers conducting OTR in their areas, unfavorable weather for selling, and not having a comfortable place when conducting OTR (On The Road).